Cинтез управления нелинейными объектами в условиях неопределенности - Кунцевич, В.М. (Проблемы управления и информатики, 2013)
Розглянуто задачу синтезу керування сім’ї нелінійних дискретних систем при вимірюванні вектора стану з обмеженими завадами. Поставлена спочатку задача синтезу керування як узагальнена задача Зубова із-за наявності нелінійності трансформувалась в симбіоз узагальнених задач Зубова–Булгакова. Основний результат статті — аналітичний роз’язок мінімаксної задачі синтезу. Control synthesis of a family of discrete-time nonlinear control systems is considered under measurements of the state vector with bounded disturbances. The stated initially problem of control synthesis as a generalization of Zubov’s problem is transformed into a symbiosis of Zubov’s problem and Bulgakov’s problem due to the presence of disturbances and non-linearity. The main result of the paper is presenting an analytical solution of the minimax synthesis problem.